1996
DOI: 10.1073/pnas.93.22.12349
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the role of proteoglycans in cation-mediated gene transfer.

Abstract: We report evidence that gene complexes, consisting of polycations and plasmid DNA enter cells via binding to membrane-associated proteoglycans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
512
3
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 741 publications
(540 citation statements)
references
References 29 publications
23
512
3
2
Order By: Relevance
“…The positive charges of cationic polymers such as polylysine can mediate vector binding to proteoglycans. Mislick and Baldeschwieler 45 showed that an excess of polylysine titrated against plasmid DNA, at an amine/nucleotide (+/À) charge ratio 41, produced optimal gene transfer and expression, while a charge ratio o1 yielded very little gene expression, in HeLa cells. The role of proteoglycans in transfection was examined by observing transfection efficiency after treatment with several glycosaminoglycan inhibitors.…”
Section: Nonreceptor Bindingmentioning
confidence: 99%
“…The positive charges of cationic polymers such as polylysine can mediate vector binding to proteoglycans. Mislick and Baldeschwieler 45 showed that an excess of polylysine titrated against plasmid DNA, at an amine/nucleotide (+/À) charge ratio 41, produced optimal gene transfer and expression, while a charge ratio o1 yielded very little gene expression, in HeLa cells. The role of proteoglycans in transfection was examined by observing transfection efficiency after treatment with several glycosaminoglycan inhibitors.…”
Section: Nonreceptor Bindingmentioning
confidence: 99%
“…For efficient nonspecific uptake, it is important for the complexes to have an overall positive charge so that they will be electrostatically attracted to the negatively charged proteoglycan cell surface. 22 It has been shown that the size of the gene delivery particles influences uptake and small particles, ~100 nm, are taken up the best. 18 However, there are conflicting reports over whether smaller or larger particles exhibit higher overall transfection.…”
mentioning
confidence: 99%
“…11,12 The transfection efficiency of the monomolecular complexes was only slightly above that of naked DNA. Indeed, being devoid of a cationic surface charge (the measured zeta potential (approximately Ϫ45 mV) was even indicative of a strong anionic surface charge), these particles are unable to bind to cell-surface heparan sulfate polyanions.…”
Section: Gene Delivery To Cells In Culturementioning
confidence: 98%